Radio observations of evaporating objects in the Cygnus OB2 region - Isequilla, Natacha Laura (2019)
We present observations of the Cygnus OB2 region obtained with the Giant Metrewave Radio Telescope (GMRT) at frequencies of 325 and 610 MHz. In this contribution we focus on the study of proplyd-like objects (also known as free-floating evaporating gas globules or frEGGs) that typically show an extended cometary morphology. We identify eight objects previously studied at other wavelengths and derive their physical properties by obtaining their optical depth at radio-wavelengths. Using their geometry and the photoionization rate needed to produce their radio-continuum emission, we find that these sources are possibly ionized by a contribution of the stars Cyg OB2 #9 and Cyg OB2 #22. Spectral index maps of the eight frEGGs were constructed, showing a flat spectrum in radio frequencies in general. We interpret these as produced by optically thin ionized gas, although it is possible that a combination of thermal emission, not necessarily optically thin, produced by a diffuse gas component and the instrument response (which detects more diffuse emission at low frequencies) can artificially generate negative spectral indices. In particular, for the case of the Tadpole we suggest that the observed emission is not of non-thermal origin despite the presence of regions with negative spectral indices in our maps.